Review of Ayurvedic Herbal Drugs for Management of Insomnia (Anidra) Along with their Experimental Studies (International Journal of Ayurveda and Pharma Research, 2023)
Ayurveda “Science of life” is a unique combination of science and philosophy that balances the holistic aspects of health i.e. physical, mental, emotional and spiritual. Its aim is to promote and preserve physical and mental health and cure of ailments too. In order to lead a good quality of life both physical and mental health of a person should be maintained in good conditions. Now a days, even people know the importance of mental health as due to their busy lifestyle usually they succumb to unhealthy lifestyle which later pose harm to their health. Due to extreme stress in life people are becoming susceptible to various mental and lifestyle health issues like anxiety, depression, HTN, Diabetes and insomnia. Insomnia is defined as a condition where a person is unable to sleep or does not have a sound and sufficient sleep and wakes up usually tired and exhausted. The general causes of insomnia include stressful lifestyle, environmental influence, mental tension, changed food habits or any mental trauma. It is generally of two types: acute insomnia and chronic insomnia. The acute insomnia is referred to a condition one with short duration of few days to few weeks and the second chronic insomnia is which lasts for longer duration of few months to even years. Some of the major symptoms of insomnia include: difficulty in falling asleep at night, sleeplessness, waking up abruptly while sleeping and then not being able to fall asleep again, waking up tired and exhausted, irritability, sometimes wake up with headache, less concentration and low mood throughout the day, over thinking and worry related to sleep. There are various treatments available for this ailment in the form of oral medicines and therapies. In Ayurvedic treatment for insomnia some therapies such as Shirodhara and herbal medicines like Brahmi, Ashwagandha, Sarpgandha are known to produce calming and relaxing effect and result in sound and good sleep. This paper aims to compile and review the classical literature regarding management of Anidra; scientifically reported classical and non-classical sedative herbs; and clinical trials conducted on Anidra.